Effectiveness of influenza vaccine in reducing influenza-associated hospitalizations and deaths among the elderly population; Lazio region, Italy, season 2016-2017. (3rd May 2020) - Fabiani, Massimo; Volpe, Enrico; Faraone, Maurizio; Bella, Antonino; Pezzotti, Patrizio; Chini, Francesco
ABSTRACT: Background: This study aimed to estimate influenza vaccine effectiveness (VE) in preventing influenza-related deaths and hospitalizations in the elderly population. Methods: We retrospectively analyzed the cohort of 1, 251, 218 elderly aged ≥65 years who were residing in the Lazio region in 2016–2017. We estimated influenza VE using the Cox proportional hazards model, adjusting for demographic characteristics, preexisting health-risk conditions, and prior vaccinations. Results: Estimated VE was 14% (95% confidence interval (CI): 11 to 17); 26% (95%CI: 19 to 33) in preventing influenza-related deaths and 13% (95%CI: 10 to 16) in preventing influenza-related hospitalizations. Seasonal VE was higher in the elderly vaccinated in prior seasons (VE = 20%, 95%CI: 17 to 23). We found no significant differences in effectiveness by vaccine type, although the MF59-adjuvanted vaccine appeared more effective than other vaccines in individuals aged ≥75 years, particularly in those aged ≥90 years (VE = 18%, 95%CI: 9 to 26). Conclusions: Although VE was low, vaccination still provided benefits in preventing influenza-related hospitalizations and deaths in the elderly, particularly among those vaccinated in prior seasons. Efforts should therefore be made to improve vaccine uptake and the utilization of vaccines with greater effectiveness in the oldest elderly (e.g. high-dose and adjuvanted cell-based vaccines).